Short-term hydrographic variability in a stratified Arctic fjord - Skarðhamar, Jofrid; Svendsen, Harald (Geological Society, London, Special Publications, 2010)
Journal homepage: http://sp.lyellcollection.org/ Fjords in the Arctic often have a more complex circulation pattern than the classical two dimentional estuarine circulation. This is due to the effects of the Earth’s rotation on stratified waters in wide fjords. Observations from a semi-enclosed fjord basin, Van Mijenfjorden on Spitsbergen, show that the hydrography and circulation vary considerably on short time scales (hours) in the summer season. The depth and distribution of the low salinity upper water layer respond quickly to changes in the wind field. The Coriolis effect has an essential impact on the circulation, inducing eddy-like flow patterns, and strong cross-fjord adients. Within the upper layer, the lowest salinity values and highest temperatures were found on the northern side of the fjord in calm wind periods. When the wind was strong from west the cross-fjord gradients were reversed. Internal wave activity contributes to large vertical displacement of water below the upper layer. Knowledge of such strongly variable hydrographic conditions in fjords are important for sampling strategy and interpretation of data, for instance of primary production and sedimentation processes, and for the understanding of fjords as depositional systems.